Impacts of Gamification Learning Approach on Student’s Performance and Perception During Covid 19 Post Pandemic 2021 In Indonesia New Normal Learning Setting - Anthia Ratna; Lubna Ali Mohammed; Anitha Kirpalani; Komal Hiranandani; Laveena Tolani; Sanchita Nandi (Publikasi Indonesia, 2023)
This study aims to determine the impact of student performance and perceptions of those taught with a gamification learning approach compared to students in rote classes on their academic reading comprehension during COVID 19 Post-Pandemic 2021 in Indonesia's New Normal learning setting. A quasi-experimental study design with pre-test and post-test control groups was used. Students are allocated to one of two versions of the program's learning environment at random: the gamified version or the original non-gamified version. The results of the pre-post test through the Independent Sample T-Test found a significant value which proved that the Gamification Learning Technique was also more effective than the rote learning method. Questionnaires were used to collect data regarding opinions related to gamification elements and it was found that most students chose